2020
DOI: 10.1038/s41598-020-70241-5
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of the γ-glutamyltransferase and alanine transaminase ratio, alpha-fetoprotein, and protein induced by vitamin K absence or antagonist II in hepatitis B virus-related hepatocellular carcinoma

Abstract: Hepatocellular carcinoma is a common type of malignancy with a poor prognosis. Identification and utilisation of markers for monitoring and diagnosis are urgently needed. Alpha-fetoprotein (AFP) and Protein Induced by Vitamin K Absence or Antagonist-II (PIVKA-II) have been proved to be efficient biomarkers for hepatitis B virus (HBV)-related hepatocellular carcinoma (HCC). The combination of the two markers could improve the detection rate. However, these indicators cannot meet the need of clinical diagnosis.I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 78 publications
0
12
0
Order By: Relevance
“…ALT levels are often used to evaluate hepatocyte damage; ALT can be released from damaged hepatocytes into the blood. In acute and chronic viral hepatitis, alcoholic hepatitis, and cirrhosis, ALT levels are elevated to varying degrees; meanwhile, in patients with HCC, ALT levels tend to be within or below the normal range [25]. Based on these findings, we hypothesized that the GGT/ALT ratio may reflect the invasiveness of HCC.…”
Section: Discussionmentioning
confidence: 98%
“…ALT levels are often used to evaluate hepatocyte damage; ALT can be released from damaged hepatocytes into the blood. In acute and chronic viral hepatitis, alcoholic hepatitis, and cirrhosis, ALT levels are elevated to varying degrees; meanwhile, in patients with HCC, ALT levels tend to be within or below the normal range [25]. Based on these findings, we hypothesized that the GGT/ALT ratio may reflect the invasiveness of HCC.…”
Section: Discussionmentioning
confidence: 98%
“…The α-FP and PIVKA-II are widely used serum tumor markers, despite that facts that approximately 40% of patients with HCC have negative α-FP, the positive predictive value ofα-FP is about 9%–32%, and PIVKA-II levels are influenced by several factors other than HCC [ 21 22 23 24 25 ]. Previous studies have reported the correlations between serum α-FP and PIVKA-II levels and the size of HCC [ 21 22 23 24 25 ]. Similarly, the present study showed that serum α-FP and PIVKA-II levels in the large group were significantly higher than those in the small group.…”
Section: Discussionmentioning
confidence: 99%
“…Elevation of serum ALT levels can also be explained in a similar context. ALT is a protein that is expressed in various human tissues and organs, with the highest expression observed in the mitochondria of hepatocytes [ 23 ]. ALT can be used as a biomarker evaluating hepatocyte destruction.…”
Section: Discussionmentioning
confidence: 99%
“…However, there existed conventional prognostic indicators that are poor at predicting the prognosis of HCC after hepatectomy [3]. Alpha-fetoprotein (AFP) has been used as an indicator of HCC diagnosis and prognosis, but only 60% of patients with HCC have positive AFP [4]. Previous studies have shown that AFP-positive was associated with worse biological behavior and inferior survival compared with AFP-negative patients [5].…”
Section: Introductionmentioning
confidence: 99%